Cultural distance and entry modes in emerging markets: Empirical evidence in Vietnam - Nguyen Minh Ha; Quan Minh Quoc Binh; Pham Phi Dang (Journal of Risk and Financial Management, 2020)
Cultural distance is acknowledged as a crucial factor that significantly affects the entry mode selection of multinational enterprises. The purpose of this article is to analyze the relationship between cultural distance and entry mode choice by exploring a novel dataset of 5236 firms in Vietnam with foreign investment during the period 2005-2016. Although many studies were conducted about the cultural distance and entry mode nexus, most of the research mainly focuses on developed and developing countries, where a market economy is already established. It is important to expand the research to a transition economy such as Vietnam, where the government is committed to attracting foreign investment. The results indicate that, when the cultural difference between Vietnam and their home country is high, foreign-invested firms prefer wholly-owned subsidiaries (WOS) over equity joint ventures (EJV). The study contributes to the general understanding about cultural distance and entry mode decision of foreign-invested firms in emerging markets.
Keywords: 330; cultural distance; entry mode; equity joint venture; wholly owned subsidiary